Adherencia farmacológica en pacientes con virus de inmunodeficiencia humana. hospital José María Velasco Ibarra, 2021 - Chancusig Taipe, Alison Pamela (2021)
ABSTRACT Societies have faced various epidemics throughout history, the one caused by HIV being one of the most devastating. The innumerable advances and scientific studies, the care systems, and health personnel have always reduced their negative impact. However, in Ecuador, some localities do not have control and follow-up studies on pharmacological adherence to antiretrovirals, as is the case at the José María Velasco Ibarra General Hospital. Therefore, the current research aims to assess the quality of pharmacological commitment to antiretrovirals in patients with HIV that attended the José María Velasco Ibarra General Hospital in 2021. For this, descriptive research was undertaken, with a field design and cross-section, collecting the information through the review of the patients' medical records and applying the Simplified Medication Adherence Questionnaire (SMAQ) test. The data were analyzed in univariate and bivariate distributions. Among the results, it stands out that the best quality of adherence was in patients with treatments of 1 to 5 years, the Lamivudine + Tenofovir Disoproxil + Dolutegravir scheme and the treatment with a pill. In addition to the sociodemographic and patient-associated factors: acceptable socioeconomic level, high school studies, male sex, adults, Spanish language, indigenous and mestizo ethnicities. To carry out further studies to deepen and incorporate other additional factors, which allow us to conceive pharmacological adherence as a multifactorial and multidimensional process. Keywords: Drug Adherence, Antiretroviral, HIV. Firmado electrónicamente por: MARCELA PATRICIA GONZALEZ ROBALINO Reviewed by: Mgs. Marcela González Robalino English Professor c.c. 0603017708